A 4-year longitudinal wastewater surveillance of five gastroenteritis viruses and the correlation with clinical cases in Alberta, Canada - Judy Y. Qiu; Sudha Bhavanam; Bonita E. Lee; Rhonda J. Rosychuk; Casey R.J. Hubert; Michael D. Parkins; Graham Tipples; Angela Crowe; Xiaoli Pang (Science of The Total Environment, 2026)

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

The effect of insect food availability on songbird reproductive success and chick body condition: Evidence from a systematic review and meta‐analysis - Eliza M. Grames; Graham A. Montgomery; Casey Youngflesh; Morgan W. Tingley; Chris S. Elphick (Ecology Letters, 2023)
Reports of declines in abundance and biomass of insects and other invertebrates from around the world have raised concerns about food limitation that could have profound impacts for insectivorous species. Food availability can clearly affect species; however, there is considerable variation among studies in whether this effect is evident, and thus a lack of clarity over the generality of the relationship. To understand how decreased food availability due to invertebrate declines will affect bird populations, we conducted a systematic review and used meta‐analytic structural equation modelling, which allowed us to treat our core variables of interest as latent variables estimated by the diverse ways in which researchers measure fecundity and chick body condition. We found a moderate positive effect of food availability on chick body condition and a strong positive effect on reproductive success. We also found a negative relationship between chick body condition and reproductive success. Our results demonstrate that food is generally a limiting factor for breeding songbirds. Our analysis also provides evidence for a consistent trade‐off between chick body condition and reproductive success, demonstrating the complexity of trophic dynamics important for these vital rates.

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Cratons, kimberlites and diamonds: selected papers of the 11th International Kimberlite Conference - Thomas Stachel; D. Graham Pearson; Andrea Giuliani; Casey M. Hetman; Jaroslav (Jarek) Jakubec; Philip E. Janney; Bruce A. Kjarsgaard; Alan F. Kobussen; Jingao Liu; Oded Navon; Roberta Rudnick; David B. Snyder; et al. (Mineralogy and Petrology, 2018)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Determining the familial risk distribution of colorectal cancer: a data mining approach - Rowena Chau; Mark A. Jenkins; Daniel D. Buchanan; Driss Ait Ouakrim; Graham G. Giles; Graham Casey; Steven Gallinger; Robert W. Haile; Loic Le Marchand; Polly A. Newcomb; Noralane M. Lindor; John L. Hopper; et al. (Familial Cancer, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Interleukin-22 genetic polymorphisms and risk of colon cancer - Cheryl L. Thompson; Sarah J. Plummer; Thomas C. Tucker; Graham Casey; Li Li (Cancer Causes & Control, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

BRMS1 contributes to the negative regulation of uPA gene expression through recruitment of HDAC1 to the NF-κB binding site of the uPA promoter - Muzaffer Cicek; Ryuichi Fukuyama; Mine S. Cicek; Steven Sizemore; Danny R. Welch; Nywana Sizemore; Graham Casey (Clinical & Experimental Metastasis, 2009)

Osteopontin Knockdown Suppresses Tumorigenicity of Human Metastatic Breast Carcinoma, MDA-MB-435 - Lalita A. Shevde; Rajeev S. Samant; Jason C. Paik; Brandon J. Metge; Ann F. Chambers; Graham Casey; Andra R. Frost; Danny R. Welch (Clinical & Experimental Metastasis, 2006)

Identification of metastasis-associated proteins through protein analysis of metastatic MDA-MB-435 and metastasis-suppressed BRMS1 transfected-MDA-MB-435 cells - Muzaffer Cicek; Rajeev S. Samant; Michael Kinter; Danny R. Welch; Graham Casey (Clinical & Experimental Metastasis, 2004)

Relation of serum insulin-like growth factor-I (IGF-I) and IGF binding protein-3 to risk of prostate cancer (United States) - Li Li; Herbert Yu; Fredrick Schumacher; Graham Casey; John S. Witte (Cancer Causes & Control, 2003)

Genomic structure of TBX2 indicates conservation with distantly related T-box genes - Christine E. Campbell; Graham Casey; Kristine Goodrich (Mammalian Genome, 1998)